Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
To solve the equation [tex]\(\left(\frac{1}{9}\right)^2 = 81^{2+1} \cdot 27^{2-a}\)[/tex], we begin by rewriting the bases in terms of powers of 3.
1. Rewriting both sides of the equation:
[tex]\[ \left(\frac{1}{9}\right)^2 = \left(\frac{1}{3^2}\right)^2 = 3^{-4} \][/tex]
[tex]\[ 81^{2+1} \cdot 27^{2-a} = 81^3 \cdot 27^{2-a} \][/tex]
2. Expressing 81 and 27 as powers of 3:
- [tex]\(81 = 3^4\)[/tex]
- [tex]\(27 = 3^3\)[/tex]
3. Substitute these powers back into the equation:
[tex]\[ 3^{-4} = (3^4)^3 \cdot (3^3)^{2-a} \][/tex]
4. Simplify the exponents in the right-hand side expression:
[tex]\[ (3^4)^3 = 3^{4 \cdot 3} = 3^{12} \][/tex]
[tex]\[ (3^3)^{2-a} = 3^{3 \cdot (2-a)} = 3^{6 - 3a} \][/tex]
So the equation becomes:
[tex]\[ 3^{-4} = 3^{12} \cdot 3^{6 - 3a} \][/tex]
5. Combine the exponents on the right-hand side:
[tex]\[ 3^{-4} = 3^{12 + 6 - 3a} = 3^{18 - 3a} \][/tex]
6. Since the bases are the same, we can equate the exponents:
[tex]\[ -4 = 18 - 3a \][/tex]
7. Solve for [tex]\(a\)[/tex]:
[tex]\[ -4 = 18 - 3a \][/tex]
Subtract 18 from both sides:
[tex]\[ -4 - 18 = -3a \][/tex]
[tex]\[ -22 = -3a \][/tex]
Divide both sides by -3:
[tex]\[ a = \frac{22}{3} \approx 7.333 \][/tex]
Thus, the value of [tex]\(a\)[/tex] is approximately [tex]\(7.333\)[/tex].
So the value of [tex]\(a\)[/tex] is not listed among the given choices ([tex]\(-4, -2, 2, 6\)[/tex]). Therefore, there seems to be a misunderstanding, but the correct mathematical value is [tex]\( \boxed{ \approx 7.333 } \)[/tex].
1. Rewriting both sides of the equation:
[tex]\[ \left(\frac{1}{9}\right)^2 = \left(\frac{1}{3^2}\right)^2 = 3^{-4} \][/tex]
[tex]\[ 81^{2+1} \cdot 27^{2-a} = 81^3 \cdot 27^{2-a} \][/tex]
2. Expressing 81 and 27 as powers of 3:
- [tex]\(81 = 3^4\)[/tex]
- [tex]\(27 = 3^3\)[/tex]
3. Substitute these powers back into the equation:
[tex]\[ 3^{-4} = (3^4)^3 \cdot (3^3)^{2-a} \][/tex]
4. Simplify the exponents in the right-hand side expression:
[tex]\[ (3^4)^3 = 3^{4 \cdot 3} = 3^{12} \][/tex]
[tex]\[ (3^3)^{2-a} = 3^{3 \cdot (2-a)} = 3^{6 - 3a} \][/tex]
So the equation becomes:
[tex]\[ 3^{-4} = 3^{12} \cdot 3^{6 - 3a} \][/tex]
5. Combine the exponents on the right-hand side:
[tex]\[ 3^{-4} = 3^{12 + 6 - 3a} = 3^{18 - 3a} \][/tex]
6. Since the bases are the same, we can equate the exponents:
[tex]\[ -4 = 18 - 3a \][/tex]
7. Solve for [tex]\(a\)[/tex]:
[tex]\[ -4 = 18 - 3a \][/tex]
Subtract 18 from both sides:
[tex]\[ -4 - 18 = -3a \][/tex]
[tex]\[ -22 = -3a \][/tex]
Divide both sides by -3:
[tex]\[ a = \frac{22}{3} \approx 7.333 \][/tex]
Thus, the value of [tex]\(a\)[/tex] is approximately [tex]\(7.333\)[/tex].
So the value of [tex]\(a\)[/tex] is not listed among the given choices ([tex]\(-4, -2, 2, 6\)[/tex]). Therefore, there seems to be a misunderstanding, but the correct mathematical value is [tex]\( \boxed{ \approx 7.333 } \)[/tex].
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.